Abaca fiber as an alternative suture material a comparative study - Ramirez, Richelle Anne Mae M.; Umayam, Rose Antoinette M.; Escoto, Elmer Jesus T. (Co-author).; Ranches, Maria Karla F. (Adviser).
Abaca has long been utilized as an exportable material for textile, paper, and rope production. In a study by Alfonso & Trinidad in 1991, It was also discovered that abaca can be potential suture material that has superior tensile strength, durability, and biocompatibility. This study aims to determine the potential of abaca fibers as an intraoral suture material by testing its biologic property and if this is comparable to that of silk and nylon. Methods: Eight adult rabbits (Oryctolagus cuniculus) weighing 2-4 kilograms were the subjects of the study and ethical requirements were passed through the University of the Philippines Institutional Animal Care and Use Committee (IACUC) under the Protocol No. 2012-019. Grade EF abaca fibers (Musa textilisnee) were selected with the size closet to 3-0, which is the preferred size of suture material used in oral surgery. Three vertical incisions on the palatal mucosa of the rabbits were done after anesthesia. The incisions were sutured with silk, nylon, and abaca threaded into 1/2 round needles. The rabbits were euthanized and biopsy was done during the 3rd and 7th day for histological analysis under hematoxylin and eosin stain. Neutrophils were counted near the sutural zone and these served as the primary data. Data collected were analysed using two-day analysis of variance (ANOVA). Clinical observations were also noted throughout the duration of the study. Results: Based from the physical tests, sterilized abaca exhibited excellent tensile strength (50.61kgf/gm). However, abaca displayed poor workability due to its rough insertion to tissue because of its flat configuration. Clinically, there were no differences between abaca, nylon, and silk since all of them exhibited non-inflamed mucosa. Histologically, it was discovered that abaca had the least amount of neutropjils after 3 days with a mean neutrophil count of 54 and nylon after 7 days with a mean neutrophil count of 44. Statistically, there was no significant difference between the three suture materials (p>0.05). Conclusion: Abaca is a potential suture material because it elicited the same amount of inflammation relative to nylon and silk and is therefore biocompatible.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentistry; Abaca; Suture